Aid and Radicalization: The Case of Hamas in the West Bank and Gaza - Amit Loewenthal; Sami H. Miaari; Anke Hoeffler (Institute of Labor Economics (IZA), 2021)
In this paper we study how radical political factions secure support. In order to achieve their objective of gaining support, radical political factions can choose from a number of specific strategies. They can provide financial assistance and generate a reciprocal relationship with their beneficiaries (political clientelism). On the other hand, financial assistance from other, non-radical sources, may raise the opportunity cost from militant policies performed by radical factions, making recipients of such financial assistance less likely to support radicals (opportunity cost theory). Smaller payments may induce loyalty, especially if the assistance is part of a "club good" offered by the radical faction, (club good theory). Costly forms of political violence by the radical faction signal resolve and may attract more support, (outbidding theory). We examine all four tactics for the case of Hamas, a radical faction in the Palestinian National Authority. We exploit a unique dataset that includes the sources and extent of assistance received by Palestinian households, data on Israeli and Palestinian fatalities as well as data on the level of support for particular Palestinian factions. We find that residents of districts that receive assistance from religious charities are more likely to support Hamas, even though this support is relatively small in monetary terms. These support patterns are in line with existing theory on armed religious groups as club good providers. By comparison, residents of districts who receive more material aid from Palestinian Authority agencies are more likely to support Fatah, except in the Hamas-controlled Gaza Strip. Finally, aid from international organizations is associated with support for moderate factions and decreased support of radical factions. While it is possible that charities only target districts and households that support them, testing for reverse causality, by regressing charity support on lagged political preferences, yields no such evidence.
Keywords: D72; D74; H56; 330; Hamas; charities; radicalization; conflict; Palestine; humanitarian aid